PEDAGOGICAL-PSYCHOLOGICAL FEATURES OF DEVELOPMENT OF STUDENTS' PROFESSIONAL AUDITORY ABILITY BY MEANS OF INFORMATIONAL EDUCATIONAL RESOURCES (Web of Technology: Multidimensional Research Journal, 2024)
The educational system of Uzbekistan strives to create an educational model that meets modern global requirements and includes innovative approaches. Development of students' professional auditory skills is important for their future professional activities. Information and educational resources, including audiovisual materials, interactive programs and online platforms, play an important role in this process. This article analyzes the pedagogical and psychological features of the development of students' professional auditory ability.